Identification of a hypoxia-regulated miRNA signature in bladder cancer and a role for miR-145 in hypoxia-dependent apoptosis - Blick, C (Br J Cancer, 2015)
BACKGROUND: Hypoxia leads to the stabilisation of the hypoxia-inducible factor (HIF) transcription factor that drives the expression of target genes including microRNAs (miRNAs). MicroRNAs are known to regulate many genes involved in tumourigenesis. The aim of this study was to identify hypoxia-regulated miRNAs (HRMs) in bladder cancer and investigate their functional significance. METHODS: Bladder cancer cell lines were exposed to normoxic and hypoxic conditions and interrogated for the expression of 384 miRNAs by qPCR. Functional studies were carried out using siRNA-mediated gene knockdown and chromatin immunoprecipitations. Apoptosis was quantified by annexin V staining and flow cytometry. RESULTS: The HRM signature for NMI bladder cancer lines includes miR-210, miR-193b, miR-145, miR-125-3p, miR-708 and miR-517a. The most hypoxia-upregulated miRNA was miR-145. The miR-145 was a direct target of HIF-1α and two hypoxia response elements were identified within the promoter region of the gene. Finally, the hypoxic upregulation of miR-145 contributed to increased apoptosis in RT4 cells. CONCLUSIONS: We have demonstrated the hypoxic regulation of a number of miRNAs in bladder cancer. We have shown that miR-145 is a novel, robust and direct HIF target gene that in turn leads to increased cell death in NMI bladder cancer cell lines.